2022
DOI: 10.3389/fpubh.2022.937179
|View full text |Cite
|
Sign up to set email alerts
|

The gender peak effect: Women are most vulnerable to infections during COVID-19 peaks

Abstract: In this article, we describe a gender peak effect that women's relative share in COVID-19 infections increases when there is a sharp increase in cases, and it reaches the highest level during peak times in each wave of the COVID-19 outbreak. We demonstrate this gender peak effect by analyzing detailed, sex-disaggregated Public Health Agency of Canada (PHAC) data. The data include 1,045,998 men and women who were confirmed cases of COVID-19 from March 2020 to February 2022. We show that women's relative share i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, other studies have demonstrated a higher percentage of female patients in the population of COVID-19 patients [14,15,[31][32][33][34]. Globally, a large proportion of the health and social care workforce is represented by women, exposing them to a higher risk for morbidity, both at work and at home, when caring for sick family members [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have demonstrated a higher percentage of female patients in the population of COVID-19 patients [14,15,[31][32][33][34]. Globally, a large proportion of the health and social care workforce is represented by women, exposing them to a higher risk for morbidity, both at work and at home, when caring for sick family members [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating epidemiological evidence has shown similar infection rates of SARS-CoV-2 between males and females in general communities [23]. Nevertheless, a study using data reported by health authorities in Canada revealed that working-age women were more vulnerable to infections than were similar-aged men during the COVID-19 pandemic [24]. Women's predominant roles as caregivers both in families and workforces may expose them to an elevated risk of infection [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating epidemiological evidence has shown similar infection rates of SARS-CoV-2 between males and females in general communities [ 29 ]. Nevertheless, a study using data reported by health authorities in Canada revealed that working-age women were more vulnerable to infections than were similar-aged men during the COVID-19 pandemic [ 30 ]. Women’s predominant roles as caregivers both in families and workforces may expose them to an elevated risk of infection [ 31 ].…”
Section: Discussionmentioning
confidence: 99%